2007
DOI: 10.1371/journal.pone.0000521
|View full text |Cite
|
Sign up to set email alerts
|

Naturalised Vitis Rootstocks in Europe and Consequences to Native Wild Grapevine

Abstract: The genus Vitis is represented by several coexisting species in Europe. Our study focuses on naturalised rootstocks that originate in viticulture. The consequences of their presence to the landscape and to native European species (Vitis vinifera ssp. silvestris) are evaluated. This study compares ecological traits (seven qualitative and quantitative descriptors) and the genetic diversity (10 SSR markers) of populations of naturalised rootstocks and native wild grapevines. 18 large naturalised rootstock populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 27 publications
3
60
0
12
Order By: Relevance
“…This indicated that the large number of alleles for rootstock varieties was due to not only the largest number of individuals included in this group but also to the high genetic diversity among the accessions comprising this group. Furthermore, the allele size range for each locus in rootstock accessions was clearly larger (Supplementary Table 2), as has been reported by Arrigo and Arnold (2007). The genetic distance measured using CS Chord revealed a high level of genetic variation among the varieties tested.…”
Section: Ssr Markerssupporting
confidence: 76%
“…This indicated that the large number of alleles for rootstock varieties was due to not only the largest number of individuals included in this group but also to the high genetic diversity among the accessions comprising this group. Furthermore, the allele size range for each locus in rootstock accessions was clearly larger (Supplementary Table 2), as has been reported by Arrigo and Arnold (2007). The genetic distance measured using CS Chord revealed a high level of genetic variation among the varieties tested.…”
Section: Ssr Markerssupporting
confidence: 76%
“…Over the last 150 years, the distribution of the wild grapevine in Europe has been reduced dramatically almost to extinction, related (a) to the arrival of new pests from North America including phylloxera (Arnold et al, 2005) and (b) to hybridisation between wild European populations of V. vinifera subsp. silvestris and naturalised Vitis genotypes introduced for rootstock selection and production (Arrigo and Arnold, 2007;Di Vecchi-Staraz et al, 2009;Terral et al, 2010;Zecca et al, 2010;Ocete et al, 2011). The impact of phylloxera on the small remaining wild grapevine populations is limited because the natural habitats of wild grapevine are in areas prone to flooding that are less suitable for the pest (Terral et al, 2010;Ocete et al, 2011Ocete et al, , 2012.…”
Section: Environmental Consequencesmentioning
confidence: 99%
“…At present, grafting European varieties on pathogen-resistant rootstock is a normal procedure and many rootstock varieties have been developed by plant breeders (Arrigo & Arnold, 2007).…”
Section: Introductionmentioning
confidence: 99%